Pemulihan Pascabencana Tsunami 2018 Guna Mendukung Program Pembangunan Daerah Kabupaten Pandeglang - Aprilyanto, A; Widana, I Dewa Ketut Kerta; Subiyanto, Adi; Rahmat, Hayatul Khairul (Jagratara: Journal of Disaster Research, 2023)
Tsunami disaster on December 2018 caused by the collapse of Mount Anak Krakatau had an impact on damage and loss of life, one of which was Pandeglang Regency, Banten Province. After the tsunami disaster, the Pandeglang Regency Government carried out rehabilitation and reconstruction activities that lasted for three years from 2019 to 2021. Three years after the implementation of post-disaster recovery, the realization of Pandeglang Regency's Original Regional Revenue has shown a decline. The aim of this research is to analyze the post-tsunami recovery index from the aspects of education, health, and economy to support development programs in Pandeglang Regency. Researchers used data collection techniques through interviews, document studies, observations, and literature studies which were then analyzed using the Ina-PDRI equation. The results show the post-tsunami recovery index in 2017 (41.71), 2018 (41.06), 2019 (46.41), 2020 (47.51) and 2021 (52.64) . Post-disaster rehabilitation and reconstruction in Pandeglang Regency has recovered since the first year (in 2019), then getting better and safer in 2020 and 2021. The trend of increasing post-disaster regional development programs can be seen through the achievements The Human Development Index (IPM) of Pandeglang Regency from 2017 to 2020, but other indicators experienced a downward trend, such as the realization of Regional Original Income (PAD) from 2018 to 2020.This downward trend in PAD is due to the Covid-19 pandemic during post-disaster recovery implementation since 2020.